Evaluation and improvement of thermal performance of residential buildings in hot and dry climate with reference to Saudi Arabia - Alaboud, Mosaab (2021)
The historical low energy costs funded by high subsidies have influenced Saudi attitudes to thermal comfort. Citizens who for years were exposed to the rigours of a harsh climate understandably were willing to pay a high energy cost to achieve comfort. However, changes in the Saudi economy and reduced buying power linked to higher energy prices have made the cost of comfort an issue for societies and governments. Buildings with optimal indoor air conditioning and low fuel consumption produce less carbon dioxide emissions and thus cause less environmental pollution. There are significant demands on the building industry in Saudi Arabia, primarily relating to the extensive energy demands during the hotter parts of the year for air conditioning purposes and the use of poor-quality building materials. Throughout the country, electricity consumption increases by more than double in the summer months. Over 50% of the country’s electricity is consumed by residential buildings. Moreover, 70% of existing buildings are not fitted with resistive insulation. Given this situation, this study explores the indoor environment of residential buildings in Saudi Arabia with a particular focus on the thermal environment. The study selected four houses located in four different climatic regions as case studies. The features of the existing houses were assessed, including their design criteria, forms, materials and surrounding conditions. The investigation of these four case studies will largely aid in determining the current status of residential buildings and highlighting the indoor features that require further improvements. Thermal retrofitting of existing buildings may be an effective solution to enhancing the environmental performance of the building industry. The two primary methods used to assess the thermal indoor conditions in the study are physical measurements and computer modelling. Instruments were used to monitor the houses during both the summer and winter months. After collection, the data were presented and visualised in Excel and subsequently analysed. Thermal Analysis Software (TAS V9.4.2) was used to thermally model the houses for two purposes. Firstly, to determine the current thermal performance of buildings and secondly, to identify areas in which improvements could be made using proposed alternate materials. Through field monitoring and thermal simulation, it was clear that the most significant factor increasing A/C use was the loss/gain of heat through the building materials. Different parts of the building (including the roof, walls, ground floors and windows) were simulated using different fabric combinations to achieve the optimum cooling reduction. The findings suggest that cooling reduction of up to 79.5 % is possible. Consequently, the intensity of the proposed annual cooling for the four chosen houses ranges between 12.4 kwh/m2/y and 83 kwh/m2/y. Moreover, buildings located in the same climatic regions should also adopt similar approaches and the methods used can be transferred to other buildings in different areas. Recommendations can then be made regarding how to improve the situation. Lastly, conclusions were made in the research and areas that require further research were identified.